Diseño de un Plan de Prevención de Riesgos Laborales para el Restaurante La Parrilla de Alex (2021)
Nowadays it has become more than a legal obligation, a moral duty with the workers of a company to provide them with a safe space to perform their functions by the employer, and this is not only reduced to the physical or tangible aspect, but also to the mental and emotional well-being of the person. Taking into account the above, it does not matter in which economic sector it operates, the employer must have an occupational prevention plan that allows it to have identified, valued and evaluated those risks present in the different areas of the company, and in this way have measures or action plans that allow the elimination or at least mitigate as much as possible the causes that may originate these risks. The purpose of this project is to design an occupational prevention plan in the food sector, specifically in a restaurant, using a simple but practical methodology when it comes to identifying the dangers to which the staff is exposed and can be managed in the correct way. , thus reducing the accident rate or the appearance of diseases later in life for these people.